Morning plasma cortisol as a cardiovascular risk factor: findings from prospective cohort and Mendelian randomization studies - Crawford, Andrew A; Soderberg, Stefan; Kirschbaum, Clemens; Murphy, Lee; Eliasson, Mats; Ebrahim, Shah; Davey Smith, George; Olsson, Tommy; Sattar, Naveed; Lawlor, Debbie A; Timpson, Nicolas J; Reynolds, Rebecca M; et al. (European journal of endocrinology, 2019)
The identification of new causal risk factors has the potential to improve cardiovascular disease (CVD) risk prediction and the development of new treatments to reduce CVD deaths. In the general population, we sought to determine whether cortisol is a causal risk factor for CVD and coronary heart disease (CHD). Three approaches were adopted to investigate the association between cortisol and CVD/CHD. First, we used multivariable regression in two prospective nested case-control studies (total 798 participants, 313 incident CVD/CHD with complete data). Second, a random-effects meta-analysis of these data and previously published prospective associations was performed (total 6680 controls, 696 incident CVD/CHD). Finally, one- and two-sample Mendelian randomization analyses were performed (122,737 CHD cases, 547,261 controls for two-sample analyses). In the two prospective nested case-control studies, logistic regression adjusting for sex, age, BMI, smoking and time of sampling, demonstrated a positive association between morning plasma cortisol and incident CVD (OR: 1.28 per 1 SD higher cortisol, 95% CI: 1.06-1.54). In the meta-analysis of prospective studies, the equivalent result was OR: 1.18, 95% CI: 1.06-1.31. Results from the two-sample Mendelian randomization were consistent with these positive associations: OR: 1.06, 95% CI: 0.98-1.15. All three approaches demonstrated a positive association between morning plasma cortisol and incident CVD. Together, these findings suggest that elevated morning cortisol is a causal risk factor for CVD. The current data suggest strategies targeted at lowering cortisol action should be evaluated for their effects on CVD.